Effects of a Supportive and Educative Program on Self-Care Behaviors, Back Pain, Flexibility and Strength of Back Muscle Among Hand Weaving Workers - เพ็ญประไพ , ปิยาภรณ์; หน่อคำ , รัญชนา; พ้นภัยพาล, มุทิตา; จันทร์เป็ง, ธีรพันธ์; สุนทรานนท์ , อนงค์; สมบูรณ์ , ลาวัลย์ (Journal of Health Science of Thailand, 2026)
cative program on self-care behaviors, back pain, flexibility, and back muscle strength among hand weaving workers. The sample consisted of 45 hand weavers, divided into an experimental group (n=22) and a control group (n=23). The experimental group received a 16-week supportive and educative program based on Orem’s theory, comprising health education, 13 stretching and strengthening postures, performed 3 days per week, and 2 weekly telephone follow-ups. The control group received usual care. Research instruments included the supportive and educative program, a handbook, exercise logbooks, a self-care behavior questionnaire, a pain assessment scale, a sit-and-reach box, and a back and leg dynamometer. Data were analyzed using independent t-test and repeated measures ANOVA. The results revealed that the experimental group had significantly higher mean scores for self-care behaviors than the control group (p<0.05). Significant group-by-time interactions were found for all variables (p<0.05). Pairwise comparisons showed that the experimental group had significantly greater back muscle flexibility than the control group at weeks 8, 12, and 16 (p<0.05). Regarding back pain and back muscle strength, the experimental group showed significantly lower pain and higher strength than the control group at weeks 12 and 16 (p<0.05). Recommendations include promoting this program for sedentary occupations, and emphasizing adherence for at least 12-16 weeks.